2006
DOI: 10.1111/j.1399-3054.2006.00790.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological integration ameliorates effects of serpentine soils in the clonal herb Fragaria vesca

Abstract: Small‐scale heterogeneity in soil characteristics and the facility of clonal systems to spread may lead to situations where parent ramets in favourable microhabitats are connected to offspring in stressful conditions. Clonal plants are physiologically integrated if connections among ramets allow transport of resources. Thus, ramets in favourable habitats may provide support to developing or stressed ramets. We examined effects of integration in Fragaria vesca growing in patches of contrasting quality (potting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 58 publications
6
49
1
Order By: Relevance
“…Our integrators thus suffer a cost for allocation to poorer patches, which plasticity in allocation or limited integration could potentially ameliorate. Empirical studies have suggested that such a cost can be either present (Salzman & Parker 1985;de Kroon et al 1998) or insignificant, perhaps due to plant plasticity (Roiloa & Retuerto 2006) or partial integration (Slade & Hutchings 1987c). Plants also can avoid costs of supplementing ramets in poorer patches by avoiding growth there (Hartnett & Bazzaz 1983;Slade & Hutchings 1987a-c;Evans 1988;Sutherland & Stillman 1988;Evans & Cain 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Our integrators thus suffer a cost for allocation to poorer patches, which plasticity in allocation or limited integration could potentially ameliorate. Empirical studies have suggested that such a cost can be either present (Salzman & Parker 1985;de Kroon et al 1998) or insignificant, perhaps due to plant plasticity (Roiloa & Retuerto 2006) or partial integration (Slade & Hutchings 1987c). Plants also can avoid costs of supplementing ramets in poorer patches by avoiding growth there (Hartnett & Bazzaz 1983;Slade & Hutchings 1987a-c;Evans 1988;Sutherland & Stillman 1988;Evans & Cain 1995).…”
Section: Discussionmentioning
confidence: 99%
“…When subjected to heavy metal stress, it is likely that heavy metals reduced the ability of the plants to assimilate resources, e.g., carbon, water, or nutrients [13,20]. More biomass allocation to roots may be related to the reduction in resource uptake and photosynthesis [20]. A possibly strengthened resource supply could alleviate the heavy metal stress to a greater extent.…”
Section: Effects Of Physiological Integration On Pollutionmentioning
confidence: 99%
“…If necessary, data were Ln-transformed before analysis pollution marginally increased biomass allocation to roots (Table 1, P = 0.088). When subjected to heavy metal stress, it is likely that heavy metals reduced the ability of the plants to assimilate resources, e.g., carbon, water, or nutrients [13,20]. More biomass allocation to roots may be related to the reduction in resource uptake and photosynthesis [20].…”
Section: Effects Of Physiological Integration On Pollutionmentioning
confidence: 99%
See 2 more Smart Citations